The economics of morality - Bowen, D (Oxford Uehiro Centre for Practical Ethics, 2016)
Altruism is embedded in our biology and in our culture. We offer our bus seats to the disabled and elderly, give directions to disoriented tourists, and donate a portion of our income charity. Yet for all the good it does, there are deep problems with altruism as it is practiced today. Nearly all of us, when asked, will say that we care about practicing altruism in a way that effectively improves the lives of others. Almost none of us, when asked, can honestly say that we have made a serious effort to ensure that we are practicing altruism in a way that effectively improves the lives of others. Disparities like these are indicative of flaws in our cognitive architecture - biases which ensure that the traditional practice of altruism is incongruous with our own values. This disconnect between our values and our actions causes our altruistic efforts to help fewer people to a lesser extent than they otherwise could. I argue that traditional altruism is in need of reformation and defend a social and philosophical movement aimed at achieving this reformation known as effective altruism. The reason effective altruism is such a promising alternative to traditional altruism is its application of economic thinking to the realm of altruism and morality. An economist’s mentality is, I suggest, a necessary instrument for bridging the gap between our values and our actions, allowing us to practice altruism in a way that more effectively improves the lives of others.